THE MONTUBIA CULTURE AS A HISTORICAL MEMORY OF ART, CULTURE, IDENTITY, BELIEFS, AND VALUES - Zambrano, Lilia Moncerrate Villacis; Marcillo, Víctor Aurelio Mero; Moncayo , Juleisi Brigitte Santos; Moncayo, Angie Lisbeth Santos; Cedeño , Yeri Betzabeth Santana; Vera, Estela Alcívar (Seven Editora, 2024)
The research aimed to analyze the preservation and transmission of the unique cultural heritage to future generations, thus ensuring the appreciation of their identity, traditions, and ways of life. The methodology visualized were quantitative and qualitative methods, the technique that was used within the process was the survey, the research work was carried out from the descriptive character. For the processing of the information, the SPSS 27 software used in this research process was used, it helped through Cronbach's alpha of alpha resulting in the reliability of the Montubia culture, 950 which evidenced that the visualized instrument was reliable. The most important conclusion of the research is that it was evident that higher education students are interested in learning more about the Montubia culture, accepting that it is their pleasure to participate in these activities, where it allows them to know in more detail the significance of the Montubia culture. DOI:https://doi.org/10.56238/sevened2024.037-082